2011
DOI: 10.1353/prv.2011.0013
|View full text |Cite
|
Sign up to set email alerts
|

Son Preference in China: Why is it Stronger in Rural Areas?

Abstract: The imbalanced sex ratio of the population in China has become a serious problem for the society. In recent decades considerably more male babies than female babies have been born in China due to people's preference for having male children. This trend is more prominent in rural areas than in urban areas. In this paper, we try to understand why rural areas have stronger son preference than urban areas. We hypothesize that the relationship between residential location and son preference is mediated by education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Desire for male children was prevalent among respondents with low socio-economic status (OR 7.64 [95 percent,, Pvalue 0.000]), who rely on their male children's income in old age, which is the tradition of Pakistani society. These results are also consistent with other study results (Lei & Pals, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Desire for male children was prevalent among respondents with low socio-economic status (OR 7.64 [95 percent,, Pvalue 0.000]), who rely on their male children's income in old age, which is the tradition of Pakistani society. These results are also consistent with other study results (Lei & Pals, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…A study in China stated similar findings, correlating a participant's lower level of education with a higher prevalence of son preference (Bharati et al, 2011). Studies from China have, however, also shown a decline in son preference and gender-biased behavior, as well as an increase in literacy and an improvement in the population's socioeconomic condition (Lei & Pals, 2011). There is a need for government intervention to introduce strong policies to work on improving the literacy rate of females and to provide awareness of the importance of providing proper nutrition and health care for daughters and women via local and district health clinics, television advertisements, and print media.…”
Section: Discussionmentioning
confidence: 78%
“…One troubling finding is that girls in China are less resilient in the face of different migration experiences, in relation to life satisfaction. A probable explanation for this finding is the Chinese cultural norm that favours boys over girls, especially in rural contexts, where the practice is most prominent (Lei & Pals, ). Given the preference towards male children, boys usually receive more resources and support from their parents, and this does occur in the context of migration.…”
Section: Discussionmentioning
confidence: 99%
“… 1 See, e.g., Croll 2000; Eklund 2011a; Murphy, Tao and Lu 2011; Jin, Li and Feldman 2007; Lei and Pals 2011. …”
mentioning
confidence: 99%